Penerapan Metode Diskusi Pada Matakuliah Pendidikan Agama Islam Program Studi Akuntansi Universitas Sulawesi Barat - Said, Supardi Muh.; Nizar, Nizar (Journal of Health, Education, Economics, Science, and Technology, 2025)
This study is grounded in the significance of applying appropriate teaching methods to achieve effectiveness in the learning process, particularly in Islamic Religious Education (PAI) courses. The objective of this research is to describe the effectiveness of the discussion method in enhancing student learning outcomes in the PAI course of the Accounting Study Program at the University of West Sulawesi. This study employs a qualitative approach through field research methods. The primary instruments used were observation and in-depth interviews. Primary data were collected from students and lecturers, while secondary data were obtained through literature studies. Data analysis was conducted descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the discussion method is effective in improving students' collaboration, communication skills, critical thinking, social interaction, active participation, and self-confidence. Students also demonstrated a deeper understanding of the material and were able to apply it in real-life situations. Based on these results, it is recommended that lecturers continue to utilize and develop the discussion method in teaching, accompanied by periodic evaluations to ensure its sustained effectiveness.